Sofrimento moral em estudantes de enfermagem e medicina - Vargas, Daíse dos Santos (2019)
Among the conflicts experienced by students in the area of health, in their formative process, are ethical and moral, in which they may present different feelings and experience different forms of suffering, such as moral suffering, when they do not exercise an ethically used action. , with a feeling of helplessness. Thus, this study aimed to identify the intensity and frequency of moral distress in nursing and medical students, and how to define criteria: adapt and validate the Moral Suffering Scale for Nursing Students (ESMEE) for populations of nursing students. nursing and medicine; describe the sociodemographic and academic profile of nursing and medical students; and to identify changes between moral distress and sociodemographic and academic variables in nursing and medical students. This is a study carried out in two stages, one methodological and the other transversal, at the federal university of Rio Grande do Sul, with nursing and medical students.Data collection was carried out in April, May and June 2017, with nursing students and in October, November and December 2017 with medical students, with the application of the Moral Distress Scale for Nursing Students (ESMEE ) adapted, in addition to sociodemographic and academic issues. In the methodological analysis, the reliability of the instrument was tested using Cronbach's alpha, and exploratory factor analysis and confirmatory factor analysis were performed, and in the cross-sectional step, descriptive statistics were used, and the Kruskal-Wallis and Mann-Whitney U tests. Still, the Machine Learning Algorithm was used in order to classify the levels of intensity of moral distress in low, medium and high. 459 students participated in the study, 342 from the medical course and 117 from the nursing course. The results allowed to observe that the applied scale presented adequate validity and reliability for both students, being its final version constituted of 36 questions, grouped in four constructs, being this Commitment of the ethical dimension of care to the user, Inadequate institutional conditions for teaching the care for the user, conflicts with professional training and disrespect for the ethical dimension of professional training. Nursing students were more intense and medical students were more frequently suffering from moral distress. However, the intensity of their moral distress was assessed as average, following the parameters analyzed. With regard to the students' experience of moral suffering, they are associated with age, sex, course, semester attended, performing activities as a scholar in the academic context, and having a diagnosed pathology. Still, moral distress is related to teaching failures, disarticulation between theory and practice and the care system at the institutional and organizational levels. However, moral distress is a reality present in the context of nursing and medical academics, requiring strategies to cope with it, as well as discussions about this theme in professional training.